Preparation and modification of itaconic anhydride–methyl methacrylate copolymers - MILOS B. MILOVANOVIC; SNEZANA S. TRIFUNOVIC; LYNNE KATSIKAS; IVANKA G. POPOVIC (Journal of the Serbian Chemical Society, 2007)
The free radical copolymerisation of itaconic anhydride and methyl methacrylate in solution was studied at 60 °C. The copolymer composition was determined by 1H-NMR spectroscopy and the obtained monomer reactivity ratios were calculated, rITA = 1.35±0.11; rMMA = 0.22±0.22 (by the Fineman–Ross method) and rITA = 1.27±0.38; rMMA = 0.10±0.05 (by the Mayo–Lewis method). The synthesised copolymers were modified by reaction with di-n-butyl amine. The copolymer composition after amidation was determined by elemental analysis via the nitrogen content. Amidation of the anhydride units in the copolymers with di-n-butyl amine resulted in complete conversion to itaconamic acid.